Adopting an Experience capitalization approach in Bhutan - Wangmo, Karma (Technical Centre for Agricultural and Rural Cooperation, 2019)
My first introduction to the experience capitalization approach came out as a blessing; I was in dire need of a concrete, or at least, more structured system to guide my documentation process. When I started on the exercises in the workshop organised by CTA in Goa, I had been writing several case stories. But, because I didn't have a proper framework to guide me, I'd left much of my work half-finished. I was unhappy with it; it was incomplete because most of the papers I was writing were started on an ad hoc basis, somehow unplanned, so their quality was compromised.